Perception of faith healers of Chandannath Municipality, Jumla towards mental illness – a qualitative study - Ghimire, Sapana; Devkota, Anup; Koirala, Swikriti; Aryal, Bandana; Acharya, Dikshya (Journal of Psychiatrists' Association of Nepal, 2025)
Background: Dhami-jhankris of Nepal are the shamans who acts as mediators between spiritual world and day to day life. In Nepal dhami-jhankris are sought for treatment of ill health in particular mental illness. People visited faith healers due to their belief. Faith healing users usually do not go to doctors without the referral from their faith healers. Collaboration between biomedical care and faith healers would be beneficial to the rural communities of Nepal as it would improve the diagnosis and treatment of mental illness. Perceptions of people should be considered when formulating the psychiatric healthcare system as they serve as facilitators or barriers for achieving mental healthcare goals. This study was undertaken with the objective to explore the perception of faith healers of Jumla towards mental illness. Method and materials: Qualitative approach was used to identify the perception of faith healers towards mental illness in Chandannath Municipality, Jumla. A total of ten (6 female and 4 male) interviews were taken using non-probability purposive sampling. Interviews were conducted in local language and audio recording was also done. Data analysis was done manually by thematic analysis. Results: People of all ages visited faith healers of Chandannath, Jumla to get evaluated if their god had inflicted on them. They could associate somatic, neurological and behavior presentations with mental illness. Their regular remedies like ritual blowing and amulets blessed with mantras were affordable to general public, and were notinhumane. Faith healers worked to add followers to their deity and for the benefit of society. Most of the faith healers did not show dislike towards biomedical care. In fact, they linked their clients with hospital. Conclusion: The faith healers’ perception of mental illness and their routine interaction with mentally ill persons could be used as an opportunity to collaborate with formal health care.